Hubungan Antara Dukungan Keluarga Terhadap Kepatuhan Ibu Melaksanakan Imunisasi Dasar Pada Anak Di Desa Tigabolon Kecamatan Sidamanik Kabupaten Simalungun Tahun 2014 - MELLA RITONGA; Syarifah, MS; Tukiman, MKM (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Responsibility of the family, especially the mother to the immunization of the infant and toddler plays an important role, so that it will obtain a benefit to the success of immunization and child health improvement. Mother's level of compliance that is less about basic immunization has the effect on family support to bring the baby to a health facility to receive immunizations. This study was intended to know the relationship between family support to mother’s compliance in following basic immunization for children in Tigabolon village in 2014 . Data analysis used Chi Square test. The results showed that the frequency of submissive mother was for 34 persons ( 65.4 % ) and non-adherent for 18 persons ( 34.6 % ). Statistical test results showed the variable of family support of informational, appraisal, instrumental, and emotional had influence on maternal compliance to implement basic immunization among children in Tigabolon village, Sidamanik district in 2014. It is recommeded that health workers can improve their services in the form of giving services in health center by providing information on the health of infants and toddlers in every visit, especially related to giving immunization replications such as Hepatitis B , Polio, DPT so that mothers understand that immunization is very important for the health of their children in order to enhance maternal adherence to implement basic immunization on children in Tigabolon village in 2014. Keywords : Family support , maternal compliance